PENERAPAN SISTEM PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KOMPETENSI KINERJA KARYAWAN PT ID EXPRESS LOGISTIK INDONESIA - Fakhrudin Alimi; Wahyu Eko Pujianto (Universitas Sains dan Teknologi Komputer, 2023)
The quality of human resources HR is one of the main factory in increasing the productivity of a company’s employees. Therefore competent human resources are are needed because they can improve employee performance. The study aims to describe how the implementation of human resource development system in improving employee performance. This study used a qualitative method with descriptive analysis approach. The data used in this study are data obtainaed from primary data source through direct intervies. Then the result are used to analyze the achievement of employee performance, namely the probability of company productivity. The research result obtaines are the implementation of a human resource development system, namely training, seminars, and rewards which have a very positive effect on employee performance competencies.